Grain yield and yield attributes of new plant type and hybrid rice - Yang, Woonho; Peng, Shaobing; Laza, Rebecca C.; Visperas, Romeo M.; Dionisio-Sese, Maribel L. (Wiley, 2007)
Development of new plant types (NPTs) and hybrids are two major approaches for improving the yield potential of irrigated rice (Oryza sativa L.). This study was conducted (i) to compare grain yield and yield attributes among three high‐yielding groups of rice, namely indica inbred, indica/indica F1 hybrid, and second‐generation NPT, and (ii) to identify the morphophysiological traits responsible for the yield difference among the three groups. Fifteen genotypes, five from each of the three groups, were grown in the dry (DS) and wet seasons (WS) of 2003 and 2004 at the International Rice Research Institute, Philippines. On average, hybrids produced 11 to 14% greater grain yield than indica inbreds and NPTs in the DS. In the WS, the difference in grain yield was relatively small among the three groups. High grain yield of hybrids in the DS was the result of high number of spikelets per square meter due to a large number of spikelets per panicle and high harvest index rather than biomass production. The NPTs did not show yield advantage over the indica inbreds and demonstrated significantly lower yield than hybrids, mainly because of fewer spikelets per panicle and per square meter. Spikelet production efficiency per unit of N uptake and per unit of aboveground biomass at physiological maturity was generally higher in hybrids than indica inbreds or NPTs. Increasing harvest index and spikelet production efficiency by developing NPTs with more spikelets per panicle should be emphasized for improving the grain yield of NPTs.